NB‐UVB irradiation attenuates inflammatory response in psoriasis. Issue 4 (11th July 2020) - Ye, Jianzhou; Huang, Hong; Luo, Guangyun; Yin, Lihua; Li, Bocheng; Chen, Sixuan; Li, Hongying; Yang, Yang; Yang, Xuesong
Abstract: Psoriasis is a chronic inflammatory disease characterized by immunological imbalance and vasodilation. Many triggering factors for psoriasis initiate inflammation via the activation of NF‐κB. Narrow‐band ultraviolet B (NB‐UVB) irradiation can be used as a general treatment for psoriasis, although the molecular mechanism has not yet been determined. The aim of this study was to elucidate the potential molecular mechanism of NB‐UVB irradiation therapy on psoriasis. We collected serum samples from patients with psoriasis and healthy control, and detected the expression of inflammatory factors by ELISA. In addition, we established mouse model of psoriasis. After different doses of NB‐UVB irradiation, the proportion of CD4 +, CD8 +, and CD11c + cells in mouse spleen was detected by flow cytometry. Meanwhile, the expression of inflammatory factors in the damaged skin of mice was detected by RT‐PCR and Western blot analysis, and mouse serum levels of inflammatory factors were detected by ELISA. Our results showed that NB‐UVB irradiation regulated the expression of inflammatory factors in psoriasis patients. In mice, high‐dose NB‐UVB irradiation effectively eliminated IMQ‐induced psoriasis‐like dermatitis and inhibited the expression of pro‐inflammatory factors. In conclusion, our results indicate that NB‐UVB irradiation could regulate the expression of inflammatory factors and attenuate psoriasis plaques.